Reform of press regulation to realize responsible press coverage - mustawa mustawa (Indonesia Prime, 2020)
The Press Law, especially Article 5 paragraph (1) becomes the standard of news writing whose implementation is guided by Article 3 of the Code of Journalistic Ethics, but the standards of the journalist profession are not found provisions in the Press Law and the Code of Journalistic Ethics, thus triggering the occurrence of press coverage that does not apply the principle of presumption of innocence. The absence of such arrangements, it must be immediately corrected by reformulating the press news system in terms of regulation into Law No. 40 of 1999 on the Press that can be a solution to the complexity of problems in the Press Briefing which must certainly be based on a free and responsible news philosophy.